2020
DOI: 10.2478/cejpp-2020-0006
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of activities in later life across European regions

Abstract: The active ageing policy supports several types of activities, including labour force participation, caregiving, social participation, and physical activity. The paper illustrates the prevalence of supported activities across individual characteristics and four supra-national European regions to assess how these activities are available for specific groups of older people. The analysis draws on wave 6 from the Survey of Health, Ageing and Retirement in Europe held in 2015. A set of figures describes the availa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 59 publications
(73 reference statements)
1
4
0
Order By: Relevance
“…Further, we showed that the dominant discourses of active ageing, which so often focus on the productive definition of social participation, or generally the level of practices through the promotion of physical activity (Del Barrio et al , 2018), contribute particularly to an elitist vision of ageing that is observed essentially among a minority of the older adults: the most socio-economically favoured. In this sense, we agree with other authors describing active ageing as a product of – built by and for – the upper class (Lakomý, 2020). In addition, the focus on formal public participation tends to promote a more masculine model of ageing (Baeriswyl, 2018).…”
Section: Discussionsupporting
confidence: 93%
“…Further, we showed that the dominant discourses of active ageing, which so often focus on the productive definition of social participation, or generally the level of practices through the promotion of physical activity (Del Barrio et al , 2018), contribute particularly to an elitist vision of ageing that is observed essentially among a minority of the older adults: the most socio-economically favoured. In this sense, we agree with other authors describing active ageing as a product of – built by and for – the upper class (Lakomý, 2020). In addition, the focus on formal public participation tends to promote a more masculine model of ageing (Baeriswyl, 2018).…”
Section: Discussionsupporting
confidence: 93%
“…We grouped the 27 countries into four European regions, based on recent SHARE studies [29] , [30] and according to the European welfare regime typologies, which was first developed and classified by Esping-Andersen [31] and later redefined and extended to cover Southern Europe [32] and Central and Eastern Europe [33] , [34] , [35] , [36] . Thus, the countries are grouped into four regions: 1) The Western European region (Germany, The Netherlands, France, Belgium, Luxembourg, Switzerland, and Austria) referring to the Western European or Bismarckian countries, 2) the Southern European region (Spain, Portugal, Malta, Italy, Greece, and Cyprus) referring to the Southern or Mediterranean countries, 3) the Central and Eastern European region (Estonia, Latvia, Lithuania, Poland, Czech Republic, Slovakia, Slovenia, Hungary, Croatia, Romania, and Bulgaria) referring to the Central and Eastern European or the post-communist countries, and 4) the Northern European region (Denmark, Sweden, and Finland) referring to the Northern European or Scandinavian countries [32] , [34] , [36] .…”
Section: Methodsmentioning
confidence: 99%
“…The six European countries were selected based on geographical location, as well as a typology of European welfare regimes [ 40 , 41 ]: Sweden from Northern Europe; Czech Republic and Estonia from Eastern Europe/post-communist countries; Greece and Spain from Southern Europe, and France from Western Europe.…”
Section: Methodsmentioning
confidence: 99%